Crime, meaning in life and well-being in three residential areas in Penang, Malaysia - Hashim, Intan Hashimah Mohd; Zaharim, Norzarina Mohd; Karupiah, Premalatha; Selamat, Nor Hafizah; Endut, Noraida; Azmawati, Azman Azwan (Universiti Sains Malaysia, 2016)
being. Crime as part of life’s negative experiences and meaning in life as part of the personal positive attributes can be related to constructs of well-being including affect, life satisfaction and subjective happiness. Semi-structured interviews assessing experience of crime, meaning in life, negative affect associated with crime, life satisfaction and subjective happiness were conducted with 240 residents from 3 urban residential areas in Penang Island, Malaysia. The three urban residential areas represented low, medium and high-cost categories. We argue that people in these different residential areas might have different experiences associated with crime. The study found some significant relationships between the constructs and evidences for specific experiences among people living in different residential areas. These findings highlight the need to understand the complex relationships between experience of crime, meaning in life and well-being among people living in different residential areas.